Adaptive human bodies and adaptive built environments for enriching futures - Andres, Josh (Frontiers in Computer Science, 2022)
As humans, we spend most of our lives inside human-built environments, such as homes, offices and schools. In these built environments, humans co-create and share a collective awareness, social practices and knowledge while computing machinery is designed to maintain the built environment and support our interactions. Effects of these technologically enriched built environments on humans are how our bodies adapt to the practices they promote and how these practices, in return, affect the built environment and the natural environment. This perspective paper uses inbodied interaction to frame the constant adaption of our bodies to our surrounding environment as an opportunity to inform the design of technology and its practices and offer a vision where humans, the built environment, and the natural environment coexist in a mutually beneficial relationship.